CfDNA in pancreatic neuroendocrine carcinoma management with Cushing's syndrome. Issue 1 (9th August 2021) - Gerard, Laura; Barthelemy, David; Gauthier, Arnaud; Hervieu, Valerie; Lopez, Jonathan; Gibert, Benjamin; Lasolle, Helene; Chardon, Laurence; Garcia, Jessica; Raverot, Gérald; Payen, Léa; Walter, Thomas
Abstract : Summary: We report a case of metastatic pancreatic neuroendocrine carcinoma associated with paraneoplastic Cushing's syndrome, successively treated with five lines of treatment (platin-etoposide, LV5FU2-dacarbazine, FOLFIRINOX, pembrolizumab, and paclitaxel) and anti-secretory treatment. Circulating-free DNA (cfDNA) was analysed at each morphological evaluation starting from the second-line treatment. cfDNA changes were well correlated with the disease course, and cfDNA may be used as a predictive marker and/or as an early marker of response. In addition, the absolute count of atypical cells was elevated upon disease progression. Learning points: cfDNA changes were well correlated with the Cushing's syndrome course and with the tumour burden changes assessed by laboratory markers and by RECIST criteria. cfDNA analysis was used to determine the pharmacogenetic patterns of the present patient. An elevated number of atypical circulating cells was noticed upon disease progression.